2005
DOI: 10.1149/1.2063307
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth and Characterizations of Highly Oriented BiFeO[sub 3] Thin Films

Abstract: BiFeO 3 ͑BFO͒ films of pure perovskite phase were deposited on Pt/TiOx/SiO 2 /Si ͑Pt͒, LaNiO 3 /Pt/TiOx/SiO 2 /Si ͑LNO͒, and BaPbO 3 /Pt/TiOx/SiO 2 /Si ͑BPO͒ substrates by rf magnetron sputtering. The BFO film was grown with random orientations on Pt whereas highly ͑100͒-oriented and ͑111͒-oriented ones were obtained on LNO and BPO, respectively. The influence of the bottom electrode on crystal growth, surface topography, leakage behavior, dielectric and ferroelectric properties was investigated. Twice remnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 24 publications
(50 reference statements)
2
23
0
Order By: Relevance
“…The (1 1 1) peak intensity first increases with increasing deposition temperature, reaches a maximum value at T d = 590°C, before it decreases with further increase in the deposition temperature. This phenomenon is similar to what has been observed with the BFO thin film buffered by BaPbO 3 underlayer [10], confirming that the deposition temperature plays an important role in the orientation development of the BFO thin film, when deposited on the SRO-buffered Pt/TiO 2 /SiO 2 /Si(1 0 0) substrate. The film texture is also dependent on the deposition temperature.…”
Section: Methodssupporting
confidence: 86%
“…The (1 1 1) peak intensity first increases with increasing deposition temperature, reaches a maximum value at T d = 590°C, before it decreases with further increase in the deposition temperature. This phenomenon is similar to what has been observed with the BFO thin film buffered by BaPbO 3 underlayer [10], confirming that the deposition temperature plays an important role in the orientation development of the BFO thin film, when deposited on the SRO-buffered Pt/TiO 2 /SiO 2 /Si(1 0 0) substrate. The film texture is also dependent on the deposition temperature.…”
Section: Methodssupporting
confidence: 86%
“…Today, much progress has been made in understanding the structure, properties, and growth of thin films of BiFeO 3 . High quality epitaxial BiFeO 3 films have been grown via molecular beam epitaxy [115,116], pulsed laser deposition [17,117], radio-frequency (RF) sputtering [118,119], metal-organic chemical vapor deposition (MOCVD) [120,121], and chemical solution deposition (CSD) [122] on a wide range of substrates including traditional oxide substrates as well as Si [117,123] and GaN [124]. This work has shown that high quality films, like those shown in Fig.…”
Section: Bifeo 3 Thin Filmsmentioning
confidence: 99%
“…In addition, the expected stress state would be compressive. Although previous work used thin SrRuO 3 -buffered layers (10-80 nm thick) as the bottom electrode in BFO films and varied the strain state by using different substrates, such as SrTiO 3 , LaAlO 3 , YAlO 3 , and Pt, [18][19][20][21] the effects of conductive buffer layers on the performance of BFO thin films has not yet been studied systematically.…”
Section: 2mentioning
confidence: 99%